The Contribution of School in Physical Activity Levels among Students Aged 10-12 Years Old. Epidemiological Study - Tambalis Κωνσταντίνος; Papoutsakis Σοφία; Sidossis Λάμπρος (Inquiries in Physical Education and Sport, 2016)
Physical activity (PA) is a parameter of children’s life which straight connected to benefits of their life (protection against obesity, better psychological profile, and predisposition for increased levels of PA as adult e.t.c.). The purpose of the present study was to evaluate daily levels of PA and especially PA during school in a sample of Greek children. Epidemiological study. PA and sedentary behaviors were assessed by a self-administrated physical activity checklist, proper for children. BMI was calculated from measured body weight and height. A representative sample of Greek children aged 10 to 12 years attending fifth and sixth grade of Elementary Education (N=3195), living in rural and urban areas were enrolled. Maturation status was not evaluated due to technical reasons. Children living in rural areas had higher levels of self reported PA (p<.001) and met current PA guidelines to a greater extent than their urban counterparts (p<.05). Furthermore, boys had higher levels of total, light-to-moderate intensity and vigorous intensity PA (VPA), than girls (all p-values<.05), while comparisons didn’t reveal significant differences between students of fifth and sixth grade, by sex. Time of PA during school represents about 27% of total amount of daily PA, in both sexes. In those days that students participated in Physical Education lessons and in Extended Daily Hours program, total PA and VPA were higher in comparison with days didn’t, in both sexes (p<.001). Finally, the results showed that during school program, boys participated in a greater proportion than girls in basketball and soccer (p-values<.05), while, more girls in comparison to boys participated in volleyball, dance and skipping rope (p-values <.05). In conclusion, children living in rural area s and boys had higher levels of PA than their urban counterparts and girls, respectively. Furthermore, it seems that school plays a significant role in student’s levels of PA which could grow up further with interventions as the increase of hours in Physical Education lessons.